Technology Use in the Classroom: Preferences of Management Faculty Members - Peluchette, Joy V.; Rust, Kathleen A. (Journal of education for business, 2005)
In this study, the authors investigated faculty members' preferences regarding the use of technologies as instructional tools in management courses. They mailed surveys to 500 management faculty members nationwide; 124 were returned with usable data. Respondents indicated that course subject and classroom environmental factors did not affect their use of preferred technologies; however, time constraint was an issue for most of the faculty members, particularly for women. Female faculty members were also more likely than their male colleagues to see their perception of students' learning style as limiting the effective use of their preferred instructional technologies.